2019
DOI: 10.1021/acs.oprd.9b00377
|View full text |Cite
|
Sign up to set email alerts
|

Potential Safety Hazards Associated with Pd-Catalyzed Cross-Coupling Reactions

Abstract: The potential safety hazards associated with Pd-catalyzed cross-coupling reactions have been underappreciated and inadequately discussed. These hazards have not been universally recognized in the past decades, perhaps overshadowed by the ubiquity of this class of chemistry and the desire to pursue new scientific advancements. The awareness of these hazards is further limited by the fact that synthetic chemists who develop these types of reactions on small scales are not typically trained in reactive chemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 188 publications
0
27
0
Order By: Relevance
“…There are other thermal hazard tests available, such as accelerating rate calorimetry (ARC), reaction calorimetry, impact sensitivity or explosivity tests, but none are as ubiquitous or simple to use as the humble DSC. Recently, there have been studies seeking to characterise and compare the thermal and process hazards of compound classes, such as peptide‐coupling reagents, oxidisers, N‐heterocyclic iodanes, diazo compounds, and cage alkyl motifs; or processes such as Pd‐catalysed cross‐coupling, TIPS‐EBX and NaH with DMF/DMSO/DMAc …”
Section: Figurementioning
confidence: 99%
“…There are other thermal hazard tests available, such as accelerating rate calorimetry (ARC), reaction calorimetry, impact sensitivity or explosivity tests, but none are as ubiquitous or simple to use as the humble DSC. Recently, there have been studies seeking to characterise and compare the thermal and process hazards of compound classes, such as peptide‐coupling reagents, oxidisers, N‐heterocyclic iodanes, diazo compounds, and cage alkyl motifs; or processes such as Pd‐catalysed cross‐coupling, TIPS‐EBX and NaH with DMF/DMSO/DMAc …”
Section: Figurementioning
confidence: 99%
“…[3,4] DSC is considered ascreening technique,with limited sensitivity,but the results are accurate and robust enough to determine process temperatures to avoid thermal decomposition (often using T D24 :the temperature at which the time to maximum decomposition rate under adiabatic conditions is 24 h), [5] estimate the severity of an exotherm (often using the adiabatic temperature rise, DT ad ), [5] and even make predictions whether impact sensitivity and explosivity are aconcern by using the Yoshida correlation. [6] Such data, particularly on novel or underexplored compounds and reagents,isinformative to chemists wishing to employ new synthetic methods.T here are other thermal hazard tests available,s uch as accelerating rate calorimetry (ARC), reaction calorimetry,i mpact sensitivity or explosivity tests,b ut none are as ubiquitous or simple to use as the humble DSC.R ecently,t here have been studies seeking to characterise and compare the thermal and process hazards of compound classes,s uch as peptide-coupling reagents, [7] oxidisers, [8] N-heterocyclic iodanes, [9] diazo compounds, [10] and cage alkyl motifs; [11] or processes such as Pdcatalysed cross-coupling, [12,13] TIPS-EBX [14] and NaH with DMF/DMSO/DMAc. [15] In contrast to these in-depth studies,DSC data reported in the mainstream organic chemistry literature generally forms asmall part of amuch broader demonstration of the synthetic utility of areagent or process,perhaps used to make cautious statements about the stability or hazardous nature of ar eagent.…”
mentioning
confidence: 99%
“…During the process optimization study, we also screened the exotherm generated during the reaction, which is also an important parameter during the scale-up process and was explained recently by Yang et al 45 We did not observe any temperature excursion during the reaction.…”
Section: Psp Synthesismentioning
confidence: 99%